SIX SIGMA DMAIC APPLICATION ON SMALL BUSINESS PERFORMANCE: A CASE STUDY ON INDONESIAN’S TOBACCO COMPANY - Husada, Syafril Widya; Handriyono, Handriyono; Awwaliyah, Intan Nurul (Directorate of Academic Research and Community Services, 2020)
This study is aimed to examine the company's production performance in the quality control department by implementing the Six Sigma DMAIC Method. Research is conducted on small tobacco business namely CV SUUD for its specific cigarette product called SKM 88 Golden Taste. The cigarette production data are collected for the period of March 22, 2019 to April 22, 2019 while the data are then analyzed using Six Sigma DMAIC Method (Define, Measure, Analyze, Improve, Control). Using the descriptive method, the results show that the SKM 88 Golden Taste cigarettes produced during the period of observation contains defect such as deflated, porous, and non-sticky glue. The production performance of SKM 88 Golden Taste cigarettes in the research period is at the level of 11.353 Defects per Million Opportunities (DPMO) or equivalent to 3,78 Sigma. This finding indicates that CV SUUD lost its revenue by 25% to 40% cause by the defect in the production which is important for small company like CV SUUD to improve its quality control by refining its standard procedure as suggested by the Six Sigma evaluation.